A Novel Routing Protocol for VANETS - Wang Ying; Xu Hui-bin; Cha Dai-feng (Institute of Advanced Engineering and Science, 2013)
An effective routing protocol to the vehicular ad-hoc networks (VANETS) should have good performance whether status of the network. And the mobile AD hoc working group on network (MANETS), VANETS have special requirements of node mobility and extremely dependent on the application, and geographic routing protocol is one of the most suitable VANETS.GPSR is the most well known positioning agreement. In this study, we analyzed the blind void detouring problem, will appear devious perimeter for GPSR routing protocol when network contains routing void area, a node priority forward strategy method to solve this problem.The NS2 simulation results show that the proposed strategy can better realize packet forwarding and enhance package transportation efficiency. DOI: http://dx.doi.org/10.11591/telkomnika.v11i4.2405